Normality as a Theoretical Concept. Comment on Mehrdad Vahabi - Ekkehart Schlicht (Ludwig-Maximilians-Universität München, Volkswirtschaftliche Fakultät, 2005)
This note comments briefly on Mehdad Vahabi's article on Alfred Marshall's concept of "Normal Value." It points out, in particular, the relationship between normality and equilibrium in the context of Marshall's moving equilibrium method.
urn:nbn:de:bvb:19-epub-649-0
Keywords: B13; B41; 330; Marshall; normal value; equilibrium; moving equilibrium; temporary equilibrium; d'Alembert; Principle of Hicks-d'Alembert; ex ante - ex post